Factors influencing digital problem-solving skills among B40 children living at the Pusat Perumahan Rakyat (PPR) - Shafizan Mohamed; Saodah Wok; Wan Norshira Wan Ghazali; Nur Shakira Mohd. Nasir (Penerbit Universiti Kebangsaan Malaysia, 2022)
In Malaysia, the B40 indicates the percentage of the country's lowest-income population, sometimes known as the "Bottom 40 percent." While the Malaysian government is doing everything it can to integrate the B40s in all of its policies, one of the most difficult challenges it faces is ensuring that the B40s are up to date with the present needs of information and communication technologies. More particular, poverty frequently deprives children of positive and useful digital media experiences and skills, as well as other opportunities. These children typically do not have access to digital media and are therefore unable to fully appreciate the possibilities offered by digital technologies. This study aims to investigate the current level of digital literacy among children living in Pusat Perumahan Rakyat (PPR), a segment of the B40 group that includes children from three PPRs in the Klang Valley area. A phone survey was conducted among 308 children from three PPRs in the Klang Valley area. The Digcomp framework for digital competency was used in this study to assess the children's digital skills, with a particular emphasis on the digital problem-solving skill. Based on their informational and operational abilities, safety and security skills, communication skills, and digital participation, as well as problem-solving skills, the children were deemed to be of moderate competence. They, on the other hand, are lacking in terms of content creation and innovation. The researchers discovered that the children's problem-solving skills are significantly influenced by their other digital-literacy skills, according to the findings. The study closes by recommending the development of more inclusive digital literacy programs that are attentive to the socio-cultural milieu in which Malaysian children are raised.